Test Environments to Analyse Methodological Improvements of Cost-benefit Analysis for Transport Interventions - Juhász, Mattias; Mátrai, Tamás; Hennderson Oliveira da Cruz, Júlio; Török, Ádám (Periodica Polytechnica Transportation Engineering, 2023)
Planners and policymakers are concerned that cost-benefit analysis (CBA) rankings are so sensitive that even minor adjustments in contentious input parameters might result in drastically different policy recommendations. Although there is a need for methodological improvement, CBA seems to retain its role as the most coherent and robust framework available for project appraisal. Based on the mentioned need for improvement, this paper aims to create a test environment to analyse possible methodological advances in transport CBAs. This test environment consists of three different models based on typical transport interventions. The models have different levels of complexity and computational need. The sensitivity of each model was tested, and the most critical factors were identified. The majority of the economic benefits come from travel time savings, so the value of time was identified as the five most sensitive factors for all cases.